Use of high-volume reclaimed asphalt pavement (RAP) for asphalt pavement rehabilitation - Sabahfar, Nassim (Kansas State University, 2012)
Because of recent rises in asphalt binder prices, state agencies and contractors are now willing to use higher volumes of reclaimed asphalt pavement (RAP). In this project, the effects of increasing RAP percentage and using fractionated RAP (FRAP) in hot-mix asphalt (HMA) mixtures have been studied. Fractionation involved processing and separating of RAP materials into at least two sizes, typically a coarse fraction and a fine fraction. This study evaluated the effects of increasing the proportions of RAP and FRAP on moisture resistance, rutting, and fatigue cracking of Superpave mixtures. Furthermore, the effect of using different sources of RAP in the mix has been investigated. HMA mixtures with five varying RAP and FRAP contents (20, 30, and 40% RAP, and 30 and 40% FRAP) were studied. The Hamburg wheel-tracking device (HWTD) test (TEX-242-F), the Kansas standard test method no. 56 (KT-56), or modified Lottman test, and the dynamic modulus test (AASHTO TP: 62-03) were used to predict moisture damage, rutting potential, and fatigue cracking resistance of the mixes. HMA specimens were made based on Superpave HMA mix design criteria for 12.5-mm (1/2-inch) nominal maximum aggregate size (NMAS) and compacted using the Superpave gyratory compactor. For the first source of RAP, results of this study showed that although mixture performance declined as the percentage of RAP increased, mixtures with even 40% RAP met minimum performance requirements. The second source of RAP, however, almost failed to meet minimum requirements even at 20% RAP. Results proved the maximum percentage of RAP allowed in the mix is highly influenced by its source. Although some improvements have been observed, especially for the second source of RAP, when RAP is compared to FRAP, FRAP does not seem to considerably affect performance of the HMA mixture.
Keywords: RAP; Fractionated RAP (FRAP); HMA; HWTD test; Dynamic Modulus; Moisture Susceptibility; Civil Engineering (0543)